Rentiers, strategic public goods, and financialization in the periphery - Gabriel Porcile; Gilberto Tadeu Lima (Levy Economics Institute of Bard College, 2023)
This paper revisits a traditional theme in the literature on the political economy of development, namely how to redistribute rents from traditional exporters of natural resources toward capitalists in technology-intensive sectors with a higher potential for innovation and the creation of higherproductivity jobs. We argue that this conflict has been reshaped in the past three decades by two major transformations in the international economy. The first is the acceleration of technical change and the key role governments play in supporting international competitiveness. This role provides the strategic public goods to foster innovation and the diffusion of technology (what Christopher Freeman called "technological infrastructure"). The second is the impact of financial globalization in limiting the ability of governments in the periphery to tax and/or issue debt to finance those public goods. Capital mobility allows exporters of natural resources to send their foreign exchange abroad to arbitrate between domestic and foreign assets, and to avoid taxation. Using a macroeconomic model for a small, open economy, we argue that in this more complex international context, the external constraint on output growth assumes different forms. We focus on two polar cases: the "pure financialization" case, in which legal and illegal capital flights prevent the government from financing the provision of strategic public goods; and the "trade deficit" case, in which private firms in the more technology-intensive sector cannot import the capital goods they need to expand industrial production.
Keywords: E12; F31; F63; H41; O11^; 330; Rentiers; public goods; financial globalization; technological infrastructure; center and periphery